Analisa Faktor Penentu Tingkat Kepuasan Pasien Di Rumah Sakit Pku Muhammadiyah Bantul - Lestari, Wijayanti Puji; Sunarto, Sunarto; Kuntari, Titik (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2009)
Growing of emulation between hospitals that is increasingly tight and sharply, hence every hospital claimed to heighten competitiveness by trying gives satisfaction to all the patients. For the purpose must be known factors which influencing level of satisfaction of the patient. And is a real thing necessary for we to know what which patient we require to fulfill their satisfaction to services which we give. This research aim to know factors determining satisfaction of patient takes care of lodging and installation of emergency, also knows is there is difference of determinant level of satisfaction between patients takes care of lodging, and installation of emergency. This research done in  PKU Muhammadiyah Bantul Hospital. This research applies cross sectional research planning. Sampling method in this research is systematic random sampling.Instrument of research applied is questionair, containing patient characteristic, satisfaction determinant factors of patient, as well as satisfaction of patient. Analysis by using SPSS for windows15. Result show that determinant level of satisfaction most importantly in determining level of satisfaction of responder takes care of lodging and installation of emergency is factor reliability. Determinant level of satisfaction of patient to take care of lodging sorted from most importantly is, reliability, assurance, accessibility, responsiveness, tangible, and last of empathy. Determinant level of satisfaction of patient for IGD sorted from most importantly is, reliability, tangible, responsiveness, accessibility, assurance, and last, empathy. For takes care of lodging responder, men gender, age more than 25 years old, lower education or SMA, and production of Rp.799.999 or less, tends to satisfying to Hospital service, but it doesn't have a meaning statistically. For installation responder of Emergency, men gender, age more than 25 years old, higher education from SMA, and production more than Rp. 799999,- tends to satisfying to Hospital service, but it doesn't have a meaning statistically.Keywords : Satisfaction determinants, PKU MUHAMMADIYAH BANTUL